Exact Solutions of Generalizes the Harry Dym Equation Using Lie Group Analysis - Körpınar, Zeliha (AMER SCIENTIFIC PUBLISHERS, 2018)
In this article, Lie symmetry analysis is accomplished on generalizes Harry-Dym equation. With principle of point symmetry, vector fields of these equations are presented. Exact solutions and similarity reductions are acquired influenced by optimal system method. Finally, exact analytic solutions are regarded by applying power series method.
Keywords: Lie Group Analysis; Harry Dym Equation; Group Analysis